Factors Affecting Managerial Effectiveness at the Ministry of Interior in Saudi Arabia - Al Harbi, Mansour Mohammad; Mat, Norazuwa (UUM Press, 2012)
There are several studies that have addressed the impact of various types of factors on managerial effectiveness including leadership styles. However, this study will be different from other studies; the specific idea of this study is that leaders affect their efficiency within their organisations and influence the performance of employees and the organisations as well. Most studies have focused on the demographic and leadership context attributes such as age, education, experience, skills, etc. But the leaders in Saudi Arabia particularly in the military services like the Ministry of Interior sector have specific characteristics which may hinder their efficiency in leading the organisation on one hand and achieving its performance on the other hand.